Konseling Gizi Keluarga Pencegahan Stunting melalui Konsumsi Protein Hewani - Ravi Masitah (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Stunting has been shown to be associated with increased morbidity and mortality in children, reduced cognitive function, and an increased risk of chronic diseases in adulthood. Stunting is caused by nutrient deficiencies that last for a long time. Low intake of nutrients, especially animal protein, is a factor causing stunting in Indonesia. The family, especially parents, has a very important role in terms of selection and feeding of children. This is to ensure that children get food according to their needs, both in quality and quantity. Therefore, a solution is provided in the form of family nutrition counseling related to stunting prevention with animal protein as an effort to increase knowledge. Counseling is expected to be more optimal by using media in the form of flyers so that the message or material conveyed can be more easily understood by the target group. The target of the service activity is families who have clowns and toddlers in RT 02 Siring Agung Village, Lubuklinggau City as many as 20 families. The target of the activity was very enthusiastic about participating in the implementation of the activity because the materials, methods and media used were interesting. Nutritional counseling to prevent stunting with animal protein in clown mothers and toddlers can help increase knowledge, change attitudes and good nutritional behaviors in preparing and improving the fulfillment of children's nutrition to prevent stunting.